SHAPING THE INDIVIDUAL EDUCATIONAL TRAJECTORY OF SPECIALIZED SCHOOL STUDENTS BASED ON ARTIFICIAL INTELLIGENCE (Universal International Scientific Journal, 2026)
The article analyzes the issues of forming an individual educational trajectory of students of specialized schools based on artificial intelligence technologies from a scientific and practical perspective. Methods for determining the level of knowledge of each student, eliminating weaknesses and targeted development using adaptive educational systems and AI diagnostics are considered, and practical recommendations are developed for Academic Lyceums of the Ministry of Internal Affairs of Uzbekistan.
Keywords: artificial intelligence, individual learning trajectory, adaptive learning, digital learning, specialized